Geographical analysis of drought and its impact on vegetation and water cover in Ali Al-Gharbi district using the SPI index and the two peers NDVI and NDWI - Nadia Hatem Tuama ((Humanities, social and applied sciences) Misan Journal of Academic Studies, 2021)
Arid and semi-arid environments are characterized by what is known as climatic drought, which is one of its basic characteristics that has received great attention in recent years due to its direct impact on agricultural, economic and population activities due to the natural disasters of drought and its negative effects.The study included several axes, the first of which was to show the concept of drought, its types and forms, and then the second axis to explain the effect of climatic characteristics on the occurrence and recurrence of dry seasons in the region, while the third axis showed the concept of the Standarzid precipitation index (SPI) and the variation of its categories in the study area for the period (1988). -2018), as the fall season recorded the highest frequency of dry seasons with (51.6, 54.8) for Dahlran and Ali Al Gharbi stations, respectively. As for the fourth axis, it dealt with the impact of drought on the decline of vegetation and water cover in the dry seasons of 2018 than in the wet seasons in 2007.